Extracellular Spermine Triggers a Rapid Intracellular Phosphatidic Acid Response in Arabidopsis, Involving PLDδ Activation and Stimulating Ion Flux - Zarza, Xavier; Shabala, Lana; Fujita, Miki; Shabala, Sergey; Haring, Michel A.; Tiburcio, Antonio F.; Munnik, Teun (Frontiers in Plant Science, 2019)
Polyamines, such as putrescine (Put), spermidine (Spd) and spermine (Spm), are low-molecular-weight polycationic molecules found in all living organisms. Despite the fact that they have been implicated in various important developmental and adaptative processes, their mode of action is still largely unclear. Here, we report that Put, Spd and Spm trigger a rapid increase in the signaling lipid, phosphatidic acid (PA) in Arabidopsis seedlings but also mature leaves. Using time-course and dose-response experiments, Spm was found to be the most effective; promoting PA responses at physiological (low μM) concentrations. In seedlings, the increase of PA occurred mainly in the root and partly involved the plasma membrane polyamine-uptake transporter, RMV1. Using a differential 32Pi-labeling strategy combined with transphosphatidylation assays and T-DNA insertion mutants, we found that phospholipase D (PLD), and in particular PLDδ was the main contributor of the increase in PA. Measuring non-invasive ion fluxes (MIFE) across the root plasma membrane of wild type and pldδ-mutant seedlings, revealed that the formation of PA is linked to a gradual- and transient efflux of K+. Potential mechanisms of how PLDδ and the increase of PA are involved in polyamine function is discussed.